Numerical simulation and experimental validation study of a mixed-mode solar dryer for cocoa beans - Adeyemi, Samuel Ayobami; Obayopo, Surajudeen Olarewaju; Akharume, Felix (Journal of Postharvest Technology, 2019)
Performance of a mixed-mode solar dryer prototype for cocoa beans was optimized by geometrical optimization of the dryer using numerical  simulation. A mixed mode solar dryer was modelled, numerically simulated using computational fluid dynamic (CFD), and the thermal  performance of the modelled dryer was experimentally validated for a 50 kg thin layer mass configuration of cocoa beans under no load  condition. The simulation parameters include drying chamber cross-sectional area, drying chamber height, drying tray (plenum) position,  collector inclination angle as well as velocity of air flow. The simulated results were obtained with reasonable accuracy, and this result showed  good agreement with experimental results. In addition, the dryer temperature from experimental validation was higher than that from a similar  dryer evaluated by a previous research group from our laboratory. The simulation results show that the dryer performance is optimal at 1 m2 drying chamber cross-sectional area, 0.2 m drying chamber height and drying tray position placed at a depth 0.1 m from the bottom of the  plenum chamber. Also, optimal collector inclination of 14° was obtained. This narrow the analytical-based wide range of collector inclination  angle recommended in literatures to (α - 6.5) ≤ β ≥ (α + 6.5) of the earth polar system.
Keywords: CFD modeling; Cocoa beans; Mixed-mode solar dryer